A useful intraoperative technique for transiliac-transsacral screws: a point-to-point coaxial guide apparatus - Ze-hang Zheng; Fei Xu; Zheng-qiang Luo; Ye Ren; Tao Fu; Han-qing Xu; Bin-bin Liu (Journal of Orthopaedic Surgery and Research, 2021)
Abstract Background The transiliac-transsacral screw placement is a clinical challenge for surgeons. This study explored a point-to-point coaxial guide apparatus assisting the transiliac-transsacral screw insertion and aimed to investigate the feasibility and accuracy of the guide apparatus in the treatment of posterior ring unstable pelvic fracture compared with a free-hand technique. Methods A retrospective study was performed to evaluate patients treated with transiliac-transsacral screws assisted by the point-to-point coaxial guide apparatus or free-hand technique. The intraoperative data of operative time and radiation exposure times were recorded. Postoperative radiographs and CT scans were performed to scrutinize the accuracy of screws position. The quality of the postoperative fracture reduction was assessed according to Matta radiology criteria. The pelvic function was assessed according to the Majeed scoring criteria at 6 months postoperatively. Results From July 2017 to December 2019, a total of 38 patients were included in this study, 20 from the point-to-point guide apparatus group and 18 from the free-hand group. There were no significant differences between the two groups in gender, age, injury causes, pelvic fracture type, screws level, and follow-up time (P > 0.05). The average operative time of the guide apparatus group for each screw was significantly less than that in the free-hand group (25.8 ± 4.7 min vs 40.5 ± 5.1, P < 0.001). The radiation exposure times were significantly lower in the guide apparatus group than that in the free-hand group (24.4 ± 6.0 vs 51.6 ± 8.4, P < 0.001). The intraosseous and juxtacortical rate of screw placement (100%) higher than in the free-hand group (94.4%). Conclusion The point-to-point coaxial guide apparatus is feasible for assisting the transiliac-transsacral screw in the treatment of posterior unstable pelvic fractures. It has the advantages of simple operation, reasonable design and no need for expensive equipment, and provides an additional surgical strategy for the insertion of the transiliac-transsacral screw.